2019
DOI: 10.1017/s2040174419000424
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient and hormone composition of milk is altered in rodent dams post-bariatric surgery

Abstract: Although bariatric surgery is approved for a woman of child-bearing age with an interest in subsequent pregnancy, reports of in utero growth issues during pregnancy have garnered a closer look at the impact of maternal surgical weight loss on the pre- and postpartum periods. Offspring of dams having received vertical sleeve gastrectomy (VSG) are born small-for-gestational age and have increased risk for metabolic syndrome later in life. Here, we aimed to determine whether the postnatal catch-up growth trajecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…This may contribute overall to the reduced short‐term feeding response in the PND14 offspring of VSG. The quality of the milk of VSG dams is also substantially different from that of lean chow‐fed or obese HFD‐fed dams 45 . In particular, the hormone content varies compared to the control groups and may not provide the nutrient or hormonal cues required for optimally feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may contribute overall to the reduced short‐term feeding response in the PND14 offspring of VSG. The quality of the milk of VSG dams is also substantially different from that of lean chow‐fed or obese HFD‐fed dams 45 . In particular, the hormone content varies compared to the control groups and may not provide the nutrient or hormonal cues required for optimally feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the milk of VSG dams is also substantially different from that of lean chow-fed or obese HFD-fed dams. 45 In particular, the hormone content varies compared to the control groups and may not provide the nutrient or hormonal cues required for optimally feeding. These may all contribute potentially to the reduced growth observed in VSG offspring in the present study.…”
Section: Vsg Pups Experience Catch-up Growth During Postnatal Lifementioning
confidence: 99%
“…Unsupervised clustering of gene expression did not separate the 2 groups, and a principal component analysis has shown that surgery type did not affect gene expression (Figure 2G). In particular, there was no difference in the transcript levels of glucose and amino acid transporters, leptin receptor, and Glp1 receptor (49,50,52,53) (Supplemental Figure 2D).…”
Section: Resultsmentioning
confidence: 99%
“…Offspring of SG-operated mice remained leaner by P21 regardless of Exendin 9-39 treatment but their weight caught up after weaning. Factors such as the composition of milk or maternal microbiome following surgery may also contribute to the postnatal differences between offspring of SG-and sham-operated mice (53,62,63).…”
Section: Discussionmentioning
confidence: 99%
“…The gestational outcomes in VSG pregnancies in rats have significant challenges that include poor in utero health [ 22 ] and reduced postnatal growth [ 23 ]. We have described macronutrient and hormone differences in the milk produced by dams with previous VSG surgery compared to controls [ 24 ]. Both ghrelin [ 25 ] and leptin [ 26 ] signaling are dysregulated in the offspring of dams with bariatric surgery prior to pregnancy.…”
Section: Introductionmentioning
confidence: 99%